2021
DOI: 10.1021/acs.est.1c01026
|View full text |Cite
|
Sign up to set email alerts
|

Data Analytics for Environmental Science and Engineering Research

Abstract: The advent of new data acquisition and handling techniques has opened the door to alternative and more comprehensive approaches to environmental monitoring that will improve our capacity to understand and manage environmental systems. Researchers have recently begun using machine learning (ML) techniques to analyze complex environmental systems and their associated data. Herein, we provide an overview of data analytics frameworks suitable for various Environmental Science and Engineering (ESE) research applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 107 publications
0
32
0
Order By: Relevance
“…The self-detection of the model uses the mean squared error (MSE), average absolute percentage (MAPE), root-mean-square error (RSME), mean absolute error (MAE), median absolute error (MedAE), and mean squared logarithmic error (MSLE) , as follows: where n is the number of decision tree models, actual­( t ) is the actual UEC of a WWTP, and predicted­( t ) is the predicted UEC of a WWTP.…”
Section: Data and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The self-detection of the model uses the mean squared error (MSE), average absolute percentage (MAPE), root-mean-square error (RSME), mean absolute error (MAE), median absolute error (MedAE), and mean squared logarithmic error (MSLE) , as follows: where n is the number of decision tree models, actual­( t ) is the actual UEC of a WWTP, and predicted­( t ) is the predicted UEC of a WWTP.…”
Section: Data and Methodsmentioning
confidence: 99%
“…The self-detection of the model uses the mean squared error (MSE), average absolute percentage (MAPE), root-meansquare error (RSME), mean absolute error (MAE), median absolute error (MedAE), and mean squared logarithmic error (MSLE) 40,41 as follows:…”
mentioning
confidence: 99%
“…The rapid growth in data volume, variety, and complexity are driving the need for a robust culture of data sharing and open science, which are steadily becoming more mainstream. , This shift will allow researchers to better leverage advances in data science and accelerate the pace of research. By integrating and analyzing data sets across disciplines, new information can be revealed and new solutions identified that were not envisioned when focusing on a narrow research topic. To harness this potential, more emphasis is needed on understanding how to maximize the reuse of existing scientific data while also adapting how new research is designed and conducted to ensure data is collected with sharing in mind.…”
Section: Why Fair?mentioning
confidence: 99%
“…After the network topology and network state equations are established, the preliminary network hydraulic calculation can be carried out. After the analysis, we can get the information on the network conditions, including nodal water pressure, pipe section flow, pipe section head loss, pipe network water quality condition, water plant discharge pressure, and water plant discharge flow, etc., and we can use the modeling software to draw the corresponding parameter images for observation [24].…”
Section: Multivariate Statistical Model Design For Water Leakage Of U...mentioning
confidence: 99%